Pediatric Cardiac Tumors: A 45-year, Single-Institution Review. (April 2015) - Linnemeier, Laura; Benneyworth, Brian D.; Turrentine, Mark; Rodefeld, Mark; Brown, John
Background: Cardiac tumors in children are rare. Of the cases reported in the literature, nearly all are benign and managed conservatively. Methods: This is a retrospective, observational study of pediatric patients <18 years who presented for surgical evaluation of a cardiac tumor, between 1969 and 2014 at a tertiary care children's hospital. Presentation, pathology, management, and outcomes were evaluated. Results: Over the last 45 years, 64 patients were evaluated for surgical resection of a cardiac tumor. Rhabdomyoma was the most common neoplasm (58%), and 17% of the tumors had malignant pathologies. While 42% of benign cardiac neoplasms required surgical intervention for significant hemodynamic concerns, 73% of malignant neoplasms underwent radical excision, if possible, followed by adjuvant chemotherapy. Despite a 37% mortality in patients with malignant pathology, an aggressive surgical approach can yield long-term survival in some patients. There were no deaths among patients with benign tumors and 17% had postoperative complications mostly related to mitral regurgitation. Conclusion: Cardiac tumors in children are rare but can be managed aggressively with good outcomes. Benign tumors have an excellent survival with most complications related to tumor location. Malignant tumors have a high mortality rate, but surgery and adjuvant chemotherapy allow for prolonged survival in selected patients.